Managing teacher workload : work-life balance and well-being - Bubb, Sara (Paul Chapman Pub. ; SAGE Publications, 2004)
"This book deserves to be the standard introduction to teachers' abilities to achieve a work-life balance. It reflects the challenges and the changes facing teachers, dealing effectively with both the big picture and the fine details that matter most"--Dr Mary Bousted, General Secretary, Association of Teachers and Lecturers.
Keywords: učitelé; management času; školní didaktika; pracovní spokojenost; teachers; time management; classroom management; job satisfaction; elektronické knihy; electronic books